RELATIONSHIP BETWEEN PERCEIVED PARENTING STYLES AND ANXIETY LEVEL AMONG YOUNG ADULTS IN KUALA LUMPUR - Balaji, Aishwarya; Sani, Raihan Munira Moh (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Parenting styles shape an individual’s psychological development and mental well-being. This study explores the relationship between perceived parenting styles and anxiety levels among young adults in Kuala Lumpur, focusing on Baumrind’s parenting styles (authoritative, authoritarian, permissive) and their correlation with anxiety measured through the Generalized Anxiety Disorder 7 (GAD-7). Using a cross-sectional survey design, data were collected from 112 participants aged 18 to 25. Findings revealed significant gender differences in anxiety levels, maternal tendencies toward permissive parenting, and the protective role of authoritative parenting in reducing anxiety. These findings affect family dynamics, mental health interventions, and parenting education initiatives.